DERIVAS DE LA REFORMA DE LA NEGOCIACIÃ“N COLECTIVA EN ESPAÃ‘A: UN ADIÃ“S A LA INTANGIBILIDAD IN PEIUS DE LAS NORMAS MÃNIMAS EN MATERIA DE PREVENCIÃ“N DE RIESGOS LABORALES ESTABLECIDAS POR LOS CONVENIOS SECTORIALES - Giménez, Amparo Garrigues (European Scientific Journal, ESJ, 2014)
Distribution and structural configuration prior to the reform of collective bargaining operated in Spain by Royal Decree-Law 7/2011 came characterized by a reservation and a preference of sectoral level (particularly state) versus lower, on issues relating to occupational safety and health. Currently, under the express purpose of "rearranging the structure of collective bargaining", amendments to the arts. 83 and 84 of the Statute of Workers entered by Royal Decree -Law 7/2011 and Law 3/2012 allow company level or group of companies agreements to change the provisions (of the state or regional sectoral agreements as well as, of course, the "losers" provincial sectoral agreements) in a wide range of subjects: some specific; and others indeterminate in a broad spectrum contained in the new letter g ) of art . 84.2. Is also expressly allowed that agreements at the regional level could affect to "untouchable subjects" set at the sectoral estate level -including minimum standards for occupational risk prevention-. All this could be possible thanks to the potential promotional concessions that can be operated through interprofessional or sectoral agreements at higher levels, conditioned by unruly decentralization demands. Traditional intangibility in peius of "minimum standards for occupational risks prevention" established by sectoral agreements could be potentially vulnerable to restrictive considerations due to collective bargaining of crisis.